Kepastian Hukum Pemberian Tarif Preferensi Perjanjian ASEAN-China Free Trade Area (ACFTA) Berdasarkan Operational Certification Prosedur (OCP) Dalam Putusan Pengadilan Pajak - Susanto, Harry; Ardiansyah, Ardiansyah (Neolectura, 2024)
The ASEAN-China Free Trade Area (ACFTA) is an agreement made by the member countries of ASEAN and the People's Republic of China with the aim of promoting a stable and harmonious economy through the free flow of goods. ACFTA also supports the idea that barriers to international trade, both tariff and non-tariff, should be reduced or even eliminated, which is known as preferential tariffs. The countries involved in the ACFTA agreement agree that the Rules of Origin (ROO) provisions are necessary to obtain preferential tariffs. ROO establishes three criteria: Origin Criteria, Consignment Criteria, and Procedural Criteria. (Procedural Criteria). The Procedural Criteria are regulated in the Operational Certification Procedures (OCP) in Appendix 1 of Attachment A of Annex 1 ROO. The OCP contains regulations regarding the time for submitting a Certificate of Origin (SKA) in order to obtain a preferential rate. There are parties that think about the implementation of OCP ACFTA in Indonesia, that further regulations on OCP cannot be made without an agreement from both sides to do so. Research conducted using a normative legal approach with data collection methods through literature study, concluded that there are still differences in the application of Operational Certification Procedures (OCP) in the imposition of preferential rates by customs officers and Tax Court judges in the region in resolving disputes regarding preferential tariff. Therefore, adjustments are needed in the legal products regarding the implementation of preferential tariff imposition, as well as an enhancement of legal understanding and reasoning in the Tax Court to provide legal certainty, justice, and benefits for all stakeholders. Keywords: ACFTA, Preferntial Tariff, OCP.